Yield stability of coro (Zea mays L.) by different crossing order of seed production. - Espinosa, Alejandro (2016)
When there is not a synchronized blooming of the progenitors of a double hybrid, the "criss cross" technique can be used, which consist of interchanging lines in a cross to eliminate the blooming differences; as it happens to the H-l37 double corn hybrid for the High Mexican Valleys (2200 to 2350 masl). This technique is used with this corn to ease the seed production process and to lessen the blooming differential. Five different combinations of the H-137 hybrid, as well as two trilineal hybrids (obtained with three out of the four lines of the mentioned double hybrid) were evaluated in this trial. The main objective was to define the productive capacity and stability of the different crossing orders. Three assays were conducted: two in Chapingo and one in Cuautitlan, Mexico; located at 2240 masl. The stability parameters of Eberhart and Russell (1966) were applied, defining the seven genotypes as 'stables'. The original crossing order (M37x M36) x (M17xM18) yielded 5.32 tlha and was numericalIy surpassed by all the other alternating combinations. The inverse crosses (M17xM18) x (M37xM38) and (M36xM 17) x (M37xM18) surpassed the original cross by 13.2% and 16.4%, respectively; although all the combinations were statistically similar. The two trilineal hybrids statistically surpassed all other crosses.